The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10533-020-00747-7
|View full text |Cite
|
Sign up to set email alerts
|

Altered litter inputs modify carbon and nitrogen storage in soil organic matter in a lowland tropical forest

Abstract: Soil organic matter (SOM) in tropical forests is an important store of carbon (C) and nutrients. Although SOM storage could be affected by global changes via altered plant productivity, we know relatively little about SOM stabilisation and turnover in tropical forests compared to temperate systems. Here, we investigated changes in soil C and N within particle size fractions representing particulate organic matter (POM) and mineral-associated organic matter (MAOM) after 13 years of experimental litter removal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 75 publications
(128 reference statements)
1
15
0
1
Order By: Relevance
“…Thus, the organic matter content in the soil was the main energy source for microbial activity that determined soil CO 2 efflux in the dry period of these forests. As previously mentioned, this period corresponded to high litter addition to the forest floor, which may stimulate soil microbial activity as shown in greater soil CO 2 release (Bréchet et al, 2017;Sayer et al, 2019Sayer et al, , 2020. Large variations in OM were observed across forest stages, which may be explained by different quantity and quality of litter input (i.e., litterfall and roots) and different rates of litter decomposition in each stage.…”
Section: The Influence Of Environmental Factors On Srmentioning
confidence: 76%
“…Thus, the organic matter content in the soil was the main energy source for microbial activity that determined soil CO 2 efflux in the dry period of these forests. As previously mentioned, this period corresponded to high litter addition to the forest floor, which may stimulate soil microbial activity as shown in greater soil CO 2 release (Bréchet et al, 2017;Sayer et al, 2019Sayer et al, , 2020. Large variations in OM were observed across forest stages, which may be explained by different quantity and quality of litter input (i.e., litterfall and roots) and different rates of litter decomposition in each stage.…”
Section: The Influence Of Environmental Factors On Srmentioning
confidence: 76%
“…We demonstrate that soil C stocks were highest in stands with a greater relative influence of light-demanding ACC tree species (Figure 5), of which many have 'high-quality' litter (Bakker et al, 2011; Figure 3), representing a substantial source of labile C compounds and nutrients for soil microbes. This major role of leaf litter decomposition in tropical forest soil carbon storage (Sayer et al, 2021) would also explain why we only observed a significant relationship between soil C stocks and tree functional composition at the soil surface (0-10 cm; Figure 5a). Thus, our results suggest that high-quality plant inputs may play a key role in soil C accumulation during secondary succession in these forests.…”
Section: Tree Functional Composition As a Driver Of Soil C Storagementioning
confidence: 79%
“…DOC and microbial biomass account for only a small proportion (often <2%) of SOC pool (Guo et al, 2020; Xu, Thornton, et al, 2013), whereas MAOC is a dominant portion (often >50%) of SOC pool and cannot be easily used by soil microbes because of physical and chemical protection (Cotrufo et al, 2019; Lavallee et al, 2020). Therefore, the increased or decreased DOC and microbial biomass and its newly‐formed necromass C under altered plant inputs will not have a significant effect on MAOC in the short term (Wu et al, 2018), and it may take a long time to observe the considerable detritus‐treatment effects on MAOC (Lajtha, Townsend, et al, 2014; Sayer et al, 2021).…”
Section: Discussionmentioning
confidence: 99%